2008
DOI: 10.1007/s00484-008-0144-9
|View full text |Cite|
|
Sign up to set email alerts
|

Weather-induced ischemia and arrhythmia in patients undergoing cardiac rehabilitation: another difference between men and women

Abstract: Given the accumulating evidence that people with underlying heart disease are a particularly vulnerable group for triggers like changing meteorological parameters, the objective of this longitudinal study was to analyze the influence of weather parameters on blood pressure, arrhythmia and ischemia in cardiovascular patients. A panel study with repeated measurements was conducted in a rehabilitation clinic in Timmendorfer Strand (Baltic Sea, Germany) with 872 cardiovascular patients. Heart rate, blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 49 publications
2
40
0
1
Order By: Relevance
“…This strongly suggests that the effects of large changes in opposite directions should be differentiated and studied separately. Moreover, Schneider et al (2008) found different reactions to temperature changes for women and men; for men/women a decrease/increase of temperature was identified as a risk factor in Schneider's study, which also points out the need for studies that are specific to individual population groups. A preliminary analysis for the population of the Czech Republic reveals that the mortality effects of sudden temperature changes are more pronounced in females than males, which is in accord with heat-related mortality (e.g.…”
Section: Seasonal Focusmentioning
confidence: 90%
See 2 more Smart Citations
“…This strongly suggests that the effects of large changes in opposite directions should be differentiated and studied separately. Moreover, Schneider et al (2008) found different reactions to temperature changes for women and men; for men/women a decrease/increase of temperature was identified as a risk factor in Schneider's study, which also points out the need for studies that are specific to individual population groups. A preliminary analysis for the population of the Czech Republic reveals that the mortality effects of sudden temperature changes are more pronounced in females than males, which is in accord with heat-related mortality (e.g.…”
Section: Seasonal Focusmentioning
confidence: 90%
“…In contrast to some other biometeorological studies that examined effects of weather changes on human mortality/ health (Květoň 1991;Kyobutungi et al 2005;Schneider et al 2008), we concentrated on relationships between mortality and weather changes in a specific part of the year (summer and/or extended summer season). This is because the effects of weather on mortality depend on season and differ in winter and summer (e.g.…”
Section: Seasonal Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that an increase in mortality is associated with exposure to low outdoor temperatures, primarily due to cardiovascular diseases, in particular from myocardial infarction and stroke (Marchant et al 1993;Näyhä 2002;Schneider et al 2008). Though the associations between cardiovascular diseases and temperature are well documented, the underlying mechanisms behind these associations are in general not very well understood.…”
Section: Introductionmentioning
confidence: 97%
“…In general, morbidity8 9 and mortality10 11 associated with heat depend on age, race, sex, class, home characteristics, access to air conditioning, general health and living in an urban area versus a rural area 12. Greater susceptibility to extreme heat has been reported for: the elderly, children, impoverished populations/those with lower socioeconomic status, pregnant women, people with chronic health conditions (eg, diabetes, mobility and cognitive constraints) and outdoor workers 8 11 13–16.…”
Section: Epidemiological Evidence From Studies On Weather and Air Polmentioning
confidence: 99%